2009
DOI: 10.1080/87568220903167182
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Relational Model to Understanding Body Image in College Women and Men

Abstract: Relational cultural theory was examined in relation to body image in two samples of college women (n = 102) and men (n = 78) from a Midwestern university. Participants completed measures of mutuality and body image satisfaction. Results revealed that low mutuality with mothers and fathers predicted body dissatisfaction in both men and women, and low mutuality with romantic partners predicted body dissatisfaction in women.For women, when the shared variance between mothers and fathers was removed, mutuality wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…Those who felt socially and emotionally supported from their mothers, family members and friends were most likely to report high levels of body image satisfaction. Specifically, students with a high level of body image satisfaction were more likely than their counterparts to talk to family members about things that are important to them and to feel loved by their mother or another family member These results lend support to those of previous studies which indicate that social support and interpersonal relationships plays an important role in body image satisfaction [18,28,30]. For instance, Ackard and colleagues reported that individuals with high body image were more likely than individuals with low body image to have positive relationships and overall satisfying relationships [30].…”
Section: Commentsupporting
confidence: 82%
See 2 more Smart Citations
“…Those who felt socially and emotionally supported from their mothers, family members and friends were most likely to report high levels of body image satisfaction. Specifically, students with a high level of body image satisfaction were more likely than their counterparts to talk to family members about things that are important to them and to feel loved by their mother or another family member These results lend support to those of previous studies which indicate that social support and interpersonal relationships plays an important role in body image satisfaction [18,28,30]. For instance, Ackard and colleagues reported that individuals with high body image were more likely than individuals with low body image to have positive relationships and overall satisfying relationships [30].…”
Section: Commentsupporting
confidence: 82%
“…Students in the present study who felt emotionally close and loved by their mothers were more likely to report a high level of body image satisfaction than students who did not feel emotionally close or loved by their mothers. Sanftner and colleagues revealed similar findings in showing that male and female university students who did not feel emotionally close to their mothers were at elevated risk for weight concerns [18]. In addition to the critical impact that parents have on their children related to emotional closeness, parents also serve as an important channel for conveying sociocultural ideals and attitudes about body image to both females and males [6].…”
Section: Commentmentioning
confidence: 82%
See 1 more Smart Citation
“…In turn, negative attitudes about one's body, or body dissatisfaction, forms a salient risk factor for disordered eating (e.g. Giles, Helme, & Krcmar, 2007;Shroff & Thompson, 2006;Stice, 2002), regularly reported by male and female adolescents (Sanftner, Ryan, & Pierce, 2009). In considering the influence of social and cultural influences on body image and eating pathology, the tripartite influence model implicates three variables in the development of body dissatisfaction and disordered eating: parents, peers, and the media (Thompson, Heinberg, Altabe, & Tantleff-Dunn, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Often, a thoughtful review of one's relational images involves an examination of experiences with the individual's family of origin. Sanftner, Ryan, and Pierce (2009) argued that attending to the impact of multiple relationships (e.g., parents, romantic partners) in clients' lives may be an important factor in addressing body image dissatisfaction, potentially preventing the development of more severe eating disorder symptoms (p. 276). Counselor-generated questions that investigate relational patterns can be useful for this initial stage.…”
Section: Individual Treatment Strategiesmentioning
confidence: 99%